An Intermediary's Learning Business System: A Case Study of Gore-Tex. Issue 3 (June 2016) - Lin, Man-Li; Oh, Eun-Teak; Liu, Ren-Jye; Hsu, Po-Kai
Abstract : Supply chain management research has gained popularity, developing from the study of short-term dyadic relationships towards examining the multiple links contained in strategic supply chain networks involving long-term collaborators. We present a study of how an intermediary firm, which has no direct contact with its end users, built up a learning business system across its supply chain network to develop sustained competitive advantage. We argue that an intermediary firm with specific internal resources can develop a learning business system in a supply chain setting, and that such a firm — where it holds capabilities to integrate collaboration and leverage competition across its value chain — can build up hard-to-imitate competences for itself and the supply chain as a whole. Our findings demonstrate that an intermediary firm can proactively lead its material suppliers, manufacturers and brands in participating in a structured learning business system to the mutual benefit of its supply chain collaborators. The system is underpinned by certification mechanisms that advance technological product skills, develop capabilities, and maintain competition by not designating particular upstream suppliers to downstream buyers, and may eventually allow the intermediary to "set the rules of the game" in its industry. Overall, we conclude that an intermediary firm can create a learning business system that develops and maintains deeply embedded competences through establishing mechanisms for both collaboration and competition across its value chain.